PERENCANAAN STRUKTUR ATAS GEDUNG RUANG KELAS MADRASAH IBTIDAIAH NEGERI ( MIN ) KOTA BUKITTINGGI - Ilham Akbar Renzano; Ishak Ishak; Deddy Kurniawan (Lembaga Penelitian dan Penerbitan Hasil Penelitian Ensiklopedia, 2022)
In line with world growth in the construction sector, Indonesia is developing and growing very rapidly. In West Sumatra itself, the need for housing as well as office buildings and learning facilities and infrastructure is currently increasing. Such is the case with